Digital Game and Mathematical Learning: Mathematic Quiz Shooting Game (MQSG) - Muzakkir, Muhammad Adib; Bahrudin, Ida Aryanie; Mohamad, Marlina; Jofri, Muhamad Hanif; Abdul Hamid, Mariam; Mohamed Nor, Mohd Faizal (Research and Innovation in Technical and Vocational Education and Training, 2021)
Abstract: Mathematics is one of the most important subjects for primary school as it requires students to do good drills and mastery so that students can achieve better results. However, the pervasive advancement of technology today demands a more effective and up-to-date approach to learning and training. Therefore, this study and development for this game application is conducted to help students in Year 6 in primary school to provide drills and vary the form of training in other platforms that use technology that is in the computer game application platform. In addition, this also gives students more effective time management while playing this game application. The development of this game application was developed by Unity software as used as the main platform, Adobe Illustrator to design icons and buttons appropriate to the game application and subsequent use of C Sharp programming using Microsoft Visual software for product functionality. Therefore, the developers use the Game Development Life Cycle (GDLC) model as a methodology and also as a guide and objective for the development of this game application. The application of this game also goes through several tests that will be evaluated by experts in related fields. According to experts, this application is very good to help students in learning mathematics subjects and can even attract the attention of the target users involved. It is hoped that this game application can give a positive impact to the students to provide appropriate preparation in facing Mathematics subject during secondary school.   Keywords: Game Apps, Mathematic, Game Development Life Cycle